Lack of Cross-Sector and Cross-Level Policy Coherence and Consistency Limits Urban Green Infrastructure Implementation in Malawi - Afionis, Stavros; Mkwambisi, David D.; Dallimer, Martin (Frontiers in Environmental Science, 2020)
The quality, quantity and accessibility of urban greenspaces and green infrastructure offer multiple benefits for city dwellers, the environment and urban sustainability. Green infrastructure provides a wide range of environmental, social, cultural, climate change adaptation, and mitigation benefits. However, for green infrastructure to do so, it needs to be integrated into national policy and city-planning strategies in ways that recognize its value and importance. Consequently, consistency and coherence between policy sectors and levels is essential. The more prominent urban green infrastructure is in national level policy, the easier it will be to ensure coherence and consistency between sectors and levels, as well as avoid national and local initiatives hindering each other's effectiveness. Integrating urban green infrastructure into planning processes should be a priority for all cities, but even more so for those in sub-Saharan Africa, which are undergoing rapid expansion. Here we focus on Malawi, one of the most rapidly urbanizing countries in sub-Saharan Africa. We collated and reviewed national-level and city-level policies and strategies, ranging from housing to transport to biodiversity, in order to determine, based on vertical and horizontal integration processes, whether urban greenspaces and green infrastructure have been incorporated into planning and management priorities. We found little evidence that urban greenspaces and green infrastructure are incorporated into national-level decision-making processes. In contrast, promoting and enhancing urban greenspace and green infrastructure was a priority in planning and strategy documents produced by the Lilongwe and Mzuzu City Councils. Better institutional coordination and policy coherence across national level sectors that affect urban greenspaces and green infrastructure is required if their multiple benefits are to be realized.